2014
DOI: 10.1002/humu.22621
|View full text |Cite
|
Sign up to set email alerts
|

Gain‐of‐Function Mutation in STIM1 (P.R304W) Is Associated with Stormorken Syndrome

Abstract: Stormorken syndrome is a rare autosomal dominant disorder characterized by a phenotype that includes miosis, thrombocytopenia/thrombocytopathy with bleeding time diathesis, intellectual disability, mild hypocalcemia, muscle fatigue, asplenia, and ichthyosis. Using targeted sequencing and whole-exome sequencing, we identified the c.910C > T transition in a STIM1 allele (p.R304W) only in patients and not in their unaffected family members. STIM1 encodes stromal interaction molecule 1 protein (STIM1), which is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
135
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(144 citation statements)
references
References 41 publications
6
135
0
3
Order By: Relevance
“…Analysis of our observations [2] together with a review of other cases [3], [4] suggests that patients with the c.910C>T mutation in STIM1 gene (p.R304W) have the same heterogeneous disease and that Stormorken syndrome (StS) and York platelet syndrome (YPS) are probably two different names for the same clinical condition. The confusion could be due to the strategy used to study platelets.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Analysis of our observations [2] together with a review of other cases [3], [4] suggests that patients with the c.910C>T mutation in STIM1 gene (p.R304W) have the same heterogeneous disease and that Stormorken syndrome (StS) and York platelet syndrome (YPS) are probably two different names for the same clinical condition. The confusion could be due to the strategy used to study platelets.…”
mentioning
confidence: 74%
“…Indeed, in patients affected with YPS platelets have been extensively studied by electron microscopy, not in the patients with StS. It should be noted that among the many biological symptoms of StS, thrombocytopenia and thrombocytopathia have been first described as major and constant defects [2], [3], [4], [5].…”
mentioning
confidence: 99%
“…Store-operated Ca 2+ entry induced by thapsigargin treatment was moderately increased in HEK293 cells transfected with this mutant [64,85,90]. These cells have shown the presence of STIM1 puncta in both thapsigargin-treated and untreated cells [65,66,85,91]. Thus, these data indicate that the Arg304Trp mutation results in constitutive Ca 2+ influx.…”
Section: Genetic Causes and Possible Molecular Mechanism Of Tubulamentioning
confidence: 85%
“…Thrombocytopenia or thrombocytopathia is frequently observed in most patients with a bleeding tendency [64,84,85]. So far, patients with the STIM1 Arg304Trp mutation reported by Misceo et al have shown hematoma after minor trauma, recurrent epistaxis, subarachnoid hemorrhage, and skin purpura [84].…”
Section: Tubular Aggregate Myopathymentioning
confidence: 99%
See 1 more Smart Citation